Human Amnion Epithelial Cells and Their Derived Exosomes Alleviate Sepsis-Associated Acute Kidney Injury via Mitigating Endothelial Dysfunction - Chi, Dongxuan; Chen, Ying; Xiang, Chengang; Yao, Weijian; Wang, Hui; Zheng, Xizi; Xu, Damin; Li, Nan; Xie, Min; Wang, Suxia; Liu, Gang; Li, Shuangling; et al. (Frontiers in Medicine, 2022)
Background Sepsis is characterized by organ dysfunction resulting from a patient’s dysregulated response to infection. Sepsis-associated acute kidney injury (S-AKI) is the most frequent complication contributing to the morbidity and mortality of sepsis. The prevention and treatment of S-AKI remains a significant challenge worldwide. In the recent years, human amnion epithelial cells (hAECs) have drawn much attention in regenerative medicine, yet the therapeutic efficiency of hAECs in S-AKI has not been evaluated. Methods Septic mice were induced by cecal ligation and puncture (CLP) operation. hAECs and their derived exosomes (EXOs) were injected into the mice via tail vein right after CLP surgery. The 7-day survival rate was observed. Serum creatinine level was measured and H&E staining of tissue sections were performed 16 h after CLP. Transmission electron microscopy was used to examine the renal endothelial integrity in CLP mice. Human umbilical vein endothelial cells (HUVECs) were treated with lipopolysaccharide (LPS) and EXOs. Zonula occludens-1 (ZO-1) localization was observed by immunofluorescence staining. Expression of phosphor-p65 (p-p65), p65, vascular cell adhesion molecule-1 (VCAM-1), and ZO-1 in the kidney were determined by Western blot. Results hAECs decreased the mortality of CLP mice, ameliorated septic injury in the kidney, and improved kidney function. More precisely, hAECs suppressed systemic inflammation and maintained the renal endothelial integrity in septic animals. EXOs from hAECs exhibited similar renal protective effects as their parental cells. EXOs maintained endothelial cell adhesion junction in vitro and inhibited endothelial cell hyperactivation in vivo. Mechanistically, EXOs suppressed proinflammatory nuclear factor kappa B (NF-κB) pathway activation in LPS-treated HUVECs and in CLP mice kidneys. Conclusion Our results indicate that hAECs and their derived EXOs may ameliorate S-AKI via the prevention of endothelial dysfunction in the early stage of sepsis in mice. Stem cell or exosome-based therapy targeting endothelial disorders may be a promising alternative for treatment of S-AKI.